A Study on Variability, Character Association and Path Analysis for Pod Yield in French Bean (Phaseolus vulgaris L.) - Panda, A.; Paul, A.; Mohapatra, P. (International Journal of Bio-resource and Stress Management, 2023)
Field experiments were conducted during two seasons i.e., rabi 2011-12 and 2012-13 at four locations of district Nayagarh of Odishato evaluate 28 genotypes of french bean for various morpho-physiological characters. The variance analysis showed that most of the traits showed moderate and moderate to high values for GCV and PCV suggesting high scope for selection. The estimates of heritability showed that most of the traits showed either moderate to high and high heritability. The characters such as green pod length, basal internodal diameter, days to 1st green pod picking, plant height, basal internodal length, green pod width, number of pods plant-1, days to 50% flowering, number of secondary branches plant-1 showed very high amount of heritability. The simultaneous studies of variability, heritability and genetic advance showed that due emphasis should be given on traits such as plant height, number of primary branches plant-1, number of secondary branches plant-1, basal intermodal length, number of pods plant-1 during selection process. The correlation studies revealed that pod yield plant-1 was positively correlated with number of pods plant-1, green pod length, number of secondary branches plant-1, number of primary branches plant-1 and negatively with days to 50% flowering, days to 1st green pod picking. The path analysis showed that direct selection for number of pods plant-1, single pod weight, and green pod length will increase pod yield plant-1 in french bean. The study revealed that due emphasis should be given on number of pods plant-1, plant height and number of secondary branches plant-1 during selection process for development of superior genotypes.